Critical assessment of extraction methods for the simultaneous determination of pesticide residues and mycotoxins in fruits, cereals, spices and oil seeds employing ultra-high performance liquid chromatography-tandem mass spectrometry - Lacina, Ondrej; Zachariasova, Milena; Urbanova, Jana; Vaclavikova, Marta; Cajka, Tomas; Hajslova, Jana (Journal of chromatography. A, 2012)
This study addresses a current trend in chemical food safety control represented by an effort to integrate analyses of various groups of food contaminants/toxicants into a single, high-throughput method. The choice of optimal sample preparation step is one of the key conditions to achieve good performance characteristics. In this context, we investigated the possibility to expand the scope of the three multi-analyte extraction procedures employed earlier in other studies for rapid isolation of either pesticides or mycotoxins from plant matrices. Following procedures were tested: A - aqueous acetonitrile extraction followed by partition (QuEChERS-like method), B - aqueous acetonitrile extraction, and C - pure acetonitrile extraction. On the list of target analytes, we had 288 pesticides (including 'troublesome' acidic, basic and base-sensitive compounds) together with 38 mycotoxins (including all EU regulated ones and many 'emerging' toxins on the European Food Safety Authority (EFSA) list). The matrices selected for the experiments, apple baby food, wheat flour, spices and sunflower seeds, represented various composition categories in terms of moisture, fat and extractable compounds (e.g. pigments and essential oils) content. In preliminary experiments, acceptable recoveries (70-120%) for most of analytes were obtained by the analysis of spiked matrices, regardless which extraction procedure was used. However, when analysing dry samples with incurred pesticide residues/mycotoxins, the method C did not enable efficient extraction of some common contaminants. Procedure A, thanks to a higher matrix equivalent compared to the method B and relatively less pronounced matrix effects, enabled lower quantification limits for all analyte/matrix combinations, with the exception of polar mycotoxins and/or pesticides. Higher recoveries for the latter group of analytes could be achieved by the method B; on the other hand, extraction efficiency of non-polar pesticides from fatty matrix was rather poor by this method.
Keywords: Sunflower Oil; Mycotoxins; slunečnicový olej; Edible Grain; jedlá semena; Hydrogen-Ion Concentration; Tandem Mass Spectrometry; Spices; vysokoúčinná kapalinová chromatografie; Food Analysis; Plant Oils; mykotoxiny; Fruit; ovoce; Chromatography, High Pressure Liquid; limita detekce; Pesticide Residues; analýza potravin; tandemová hmotnostní spektrometrie; rezidua pesticidů; oleje rostlin; koření; Limit of Detection; koncentrace vodíkových iontů